Social support for physical activity—role of Facebook with and without structured intervention - Cavallo, David N. (Transl Behav Med, 2014)
Despite their widespread use and extensive technical features, little is known about how to use online social networking sites to increase physical activity. This study aims to examine Facebook engagement among participants in the online social networking arm of a randomized controlled physical activity promotion trial (n = 67). Facebook communications were double coded and analyzed using ATLAS.ti. Regression procedures were used to determine predictors of Facebook use and associations between types of use and changes in perceived social support and physical activity. Changes in perceived social support and physical activity were more strongly associated with participants’ individual Facebook use than use of the Facebook intervention group. The way social media sites are used in intervention design could have an impact on their effects. Including existing friends in interventions and using applications that incorporate intervention activities into a more naturalistic use of Facebook may improve the efficacy of future interventions.